Incidental findings in whole-body MR imaging of a population-based cohort study: Frequency, management and psychosocial consequences - Schlett, Christopher L.; Rospleszcz, Susanne; Korbmacher, Dorina; Lorbeer, Roberto; Auweter, Sigrid; Hetterich, Holger; Selder, Sonja; Heier, Margit; Linkohr, Birgit; Weckbach, Sabine; Ertl-Wagner, Birgit; Peters, Annette; et al. (European journal of radiology, 2021)
Objectives - Management of incidental findings (IF) remains controversial but highly relevant. Our aim was to assess the frequency, management and psychosocial consequences of IF reporting in a population-based cohort study undergoing whole-body MR imaging. - Methods - The study was nested in a prospective cohort from a longitudinal, population-based cohort (KORA-FF4) in southern Germany. All MR obtained on 3T MR scanner were reviewed by board-certified radiologists regarding clinically relevant IF. A baseline and follow-up questionnaires including PHQ-9 were completed prior to and 6-month after to the scan. - Results - Of 400 participants (56.3±9.2years, 58 % male) undergoing whole-body MR, IF were found in 22 % of participants (n=89); most frequently located in the abdominal sequences. In the pre-scan survey, most participants stated as the motivation that they wanted to “contribute to a scientific purpose” (91 %), while “knowing whether I’m healthy” was the most frequent motivation reported 6 months post-scan (88 %). The desire for IF reporting increased over time (pre- vs. 6-months-post-scan), also for clinically less important IF (72 % vs. 84 %, p=0.001). Regarding psychosocial impact, a small portion (3.4 %) reported that awaiting the IF report added “definitely” or “very probably” additional stress burden. Of participants with reported IF, 56.8 % classified the results as “very helpful”. In the post-scan survey moderate depression was observed in 3.3 % and severe depression in 1.2 %. This did not differ between participants with and without reported IF. - Conclusion - In a cohort with whole-body MR imaging, the prevalence of IF was high. Participants considered reporting of IF highly important and added only minor psychological burden.
Online Publikationsdatum: 28 November 2020
Gesehen am 23.04.2022